Utilizing Comics in Arts-Informed Appreciative Inquiry: Untapped Potential When Conducting Research with Children - Jeffery Thornborrow; Douglas Gosse (Canadian Society for Studies in Education, 2020)
This paper demonstrates the potential of combining an Appreciative Inquiry (AI) methodological framework with arts-informed research methods, particularly in applying comics to the AI process where children are active participants in research. Included in this article is a review of each methodological framework and a critical exploration of the literature. It is the position of the authors that arts-informed methods applied within an AI framework offers unexplored potential for generating new ways of knowing by valuing and relying on the voices of child participants to gain different perspectives. These perspectives are crucial for research that directly impacts the child population.